Organization for Economic Co-operation and Development guidelines for learning organization in higher education and its impact on lifelong learning – evidence from Indian business schools. Issue 4 (18th February 2020) - Neelam, Netra; Sheorey, Pratima; Bhattacharya, Sonali; Kunte, Monica
Abstract : Purpose: Lifelong learning has gained significant research attention world over because of its potential to enhance and ensure continuous employability. However, role of higher education institute as a learning organization to develop lifelong learning attitudes among young adults has not been discussed much. Parameters that determine lifelong learning among working professionals or school-going children may differ from that of prospective managers studying in business schools. Organization for Economic Co-operation and Development (OECD) have given guidelines on learning organization in higher education context which has not been empirically tested. The present study aims to develop a scale on learning organization based on the OECD guideline. It also aims to explore the impact of learning organization and learning processes on lifelong learning attitude in Indian business schools. Design/methodology/approach: The present study develops a multidimensional scale to measure business schools' perceived level of performance as a learning organization from the perspective of faculty. The scale considers a learning organization as a multidimensional second-order construct comprising organizational climate for learning, leadership support for knowledge exchange, support for innovation, applied research environment and vision communication. Exploratory factor analysis (EFA) has been used to refine and validate the scale. The study also assesses the impact of business schools' performance as learning organization on perceived learning processes and lifelong learning attitude from the perspective of business school students by using structural equation modeling. Findings: The study reveals that a learning organization is characterized by organizational climate for learning, leadership support for knowledge exchange, support for innovation, applied research environment and vision communication. Learning organization determines both perceived learning processes ( ß = 0.397) and lifelong learning attitude ( ß = 0.259). The relationship between learning organization and lifelong learning partially mediates through learning processes (Sobel's statistics = 1.82, p -value = 0.068, indirect effect = 29%). Lifelong learning is characterized by self-regulated reflective learning with knowledge gained through various sources including virtual sources. Originality/value: Literature adequately speaks about various scales on learning organization, but there is no specific scale developed, so far, for higher education institutes. Thus, the unique contribution of the present study is the development of a new scale on learning organization based on OECD guidelines on higher education. The scale has been developed based on survey of faculty members and students of Indian business schools. The scale can be used to assess academicians' perception toward effectiveness of a learning organization. Such information would help in formulating strategies on what should be the characteristics of teaching–learning process, knowledge acquisition and knowledge dissemination to ensure lifelong learning and continuous employability.